2014
DOI: 10.3390/m830
|View full text |Cite
|
Sign up to set email alerts
|

6-Chloro-2-hydroxy-2-trifluoromethyl-2H-chromene-3-carboxylic acid (5-allylsulfanyl-[1,3,4]thiadiazol-2-yl)-amide

Abstract: Abstract:A new chromene containing 1,3,4-thiadiazole and trifluoromethyl(CF 3 ), 6-chloro-2-hydroxy-2-trifluoromethyl-2H-chromene-3-carboxylic acid (5-allylsulfanyl-[1,3,4]thiadiazol-2-yl)-amide was synthesized and its structure was characterized by IR,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(16 reference statements)
2
1
0
Order By: Relevance
“…In this study ,all (10) V. cholerae isolates were investigated biotyping and the results showed that all V. choleraee were O1(Eltor) serotype group (16).Our results was in agreement with the results obtained by (22) .…”
Section: Table (1): Biochemical Tests Of V Choleraee Isolatessupporting
confidence: 90%
See 2 more Smart Citations
“…In this study ,all (10) V. cholerae isolates were investigated biotyping and the results showed that all V. choleraee were O1(Eltor) serotype group (16).Our results was in agreement with the results obtained by (22) .…”
Section: Table (1): Biochemical Tests Of V Choleraee Isolatessupporting
confidence: 90%
“…Three isolates V. cholerae (3,5,6)were selected depending on results of antibiotics sensitivity tests as showed multiple -antibiotics resistance(100%). Results agreed with (22) who found that the V. choleraee isolates showed a high sensitivity to each of Ampicillin, Ciprofloxacin, Erythromycine , Tetracycline, Gentamicin and Cephalothin, and showed a low resistance (10%) and (20%) to Cefotaxime and Amikacin respectively, but disagreed with her results when she found that (80%) of the environmental isolates were resistance to Amikacin.…”
Section: Antibiotics Susceptibilitysupporting
confidence: 76%
See 1 more Smart Citation